Assessing the Bacterial Community Composition of Bivalve Mollusks Collected in Aquaculture Farms and Respective Susceptibility to Antibiotics - Vanessa Salgueiro; Lígia Reis; Eugénia Ferreira; Maria João Botelho; Vera Manageiro; Manuela Caniça (MDPI AG, 2021)
Aquaculture is a growing sector, providing several products for human consumption, and it is therefore important to guarantee its quality and safety. This study aimed to contribute to the knowledge of bacterial composition of Crassostrea gigas, Mytilus spp. and Ruditapes decussatus, and the antibiotic resistances/resistance genes present in aquaculture environments. Two hundred and twenty-two bacterial strains were recovered from all bivalve mollusks samples belonging to the Aeromonadaceae, Bacillaceae, Comamonadaceae, Enterobacteriaceae, Enterococcaceae, Micrococcaceae, Moraxellaceae, Morganellaceae, Pseudomonadaceae, Shewanellaceae, Staphylococcaceae, Streptococcaceae, Vibrionaceae, and Yersiniaceae families. Decreased susceptibility to oxytetracycline prevails in all bivalve species, aquaculture farms and seasons. Decreased susceptibilities to amoxicillin, amoxicillin/clavulanic acid, cefotaxime, cefoxitin, ceftazidime, chloramphenicol, florfenicol, colistin, ciprofloxacin, flumequine, nalidixic acid and trimethoprim/sulfamethoxazole were also found. This study detected six qnrA genes among Shewanella algae, ten qnrB genes among Citrobacter spp. and Escherichia coli, three oqxAB genes from Raoultella ornithinolytica and blaTEM-1 in eight E. coli strains harboring a qnrB19 gene. Our results suggest that the bacteria and antibiotic resistances/resistance genes present in bivalve mollusks depend on several factors, such as host species and respective life stage, bacterial family, farm's location and season, and that is important to study each aquaculture farm individually to implement the most suitable measures to prevent outbreaks.